2022
DOI: 10.1101/2022.09.08.504083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Haplotype-resolved assemblies and variant benchmark of a Chinese Quartet

Abstract: As the state-of-the-art sequencing technologies and computational methods enable investigation of challenging regions in the human genome, an update variant benchmark is demanded. Herein, we sequenced a Chinese Quartet, consisting of two monozygotic twin daughters and their biological parents, with multiple advanced sequencing platforms, including Illumina, BGI, PacBio, and Oxford Nanopore Technology. We phased the long reads of the monozygotic twin daughters into paternal and maternal haplotypes using the par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Four accompanying papers detail the establishment of the DNA 66 , RNA 67 , protein 68 and metabolite 69 reference materials, reference datasets and QC methods for each type of omics profiling. Haplotype-resolved assemblies and a variant benchmark have also been provided 70 . Another paper 71 is dedicated to benchmarking batch effect correction algorithms (BECAs) using the Quartet multi-omics data.…”
Section: Articlementioning
confidence: 99%
“…Four accompanying papers detail the establishment of the DNA 66 , RNA 67 , protein 68 and metabolite 69 reference materials, reference datasets and QC methods for each type of omics profiling. Haplotype-resolved assemblies and a variant benchmark have also been provided 70 . Another paper 71 is dedicated to benchmarking batch effect correction algorithms (BECAs) using the Quartet multi-omics data.…”
Section: Articlementioning
confidence: 99%
“…BioNano only validated 3.2% INS and 1.8% DEL over 1 kb, due to its low resolution (kb) by specific restriction enzyme cut sites and failure to accurately determine breakpoints 37 . We also validated our SV benchmark callset with Jia et al 34 , and found that 97.1% INS and 91.9% DEL were confirmed.…”
Section: Determining Structural Variant Benchmark Calls and Regionsmentioning
confidence: 53%
“…We further compared the small variants benchmark calls with high confidence call sets from two accompanying studies 33, 34 (Supplementary Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, existing benchmark studies typically rely on a single gDNA reference sample and its corresponding benchmark variants, limiting their assessment solely within prede ned high-con dence regions or benchmark regions, while disregarding variants beyond these boundaries. Recently, the Quartet project, aimed for quality control and data integration of multiomic pro ling, established a suite of DNA reference materials from four immortalized cell lines derived from a family of parents and monozygotic twins [21][22][23] . These Quartet DNA reference materials not only facilitate the evaluation of variant calling accuracy within high-con dence regions but also provide pedigree information from the Quartet family design and the Mendelian consistent rate (MCR), thereby extending performance assessment capabilities outside the high-con dence regions to evaluate the precision of variant calls 22 .…”
Section: Introductionmentioning
confidence: 99%